REKOMENDASI RANCANGAN KAMPANYE SOSIAL TEMA BODY SHAMING BAGI GENERASI Z - Wiedy Nadya Putri (Wimba : Jurnal Komunikasi Visual, 2022)
Body shaming on social media is increasingly happening and has a serious impact including feeling of shame, anxiety and decreased self-confidence which can lead to suicidal thoughts. This phenomenon is important to address considering the prevalence of this happening on social media which will have a big influence on generation Z who was born and collided in the era of digital technology development. They live in two worlds namely the real world and the virtual world. So that bad comments received in cyberspace will have a direct effect on their reall world. Through this research, a campaign plan and strategy will be made to increase the confidence of generation Z in order to avoid the negative impacts of body shaming. This campaign was designed through the Ostergaard campaign method. The result of this research are strategies, concepts and media campaign design.